Implementasi Skema Anti-Collision Menggunakan Metode TDMA dan TPSN pada Sistem WSN Berbasis LoRa - Fajar Hamid Embutara Ratuloli; Agung Setia Budi; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The usage of LoRa-based Wireless Sensor Network (WSN) overcomes a common problem of WSN, that its communication capabilities over a near range. LoRa is a radio spectrum modulation technology that accommodates long distances communication with low power consumption. But the current weakness of system, the delivery data is interfering with each other which causes data loss. Time Division Multiple Access (TDMA) method is used to avoid this problem. TDMA is a scheduling method that divides by timeslot, and it compatible with LoRa because it works on single frequency. In a TDMA implementation, all device times must be synchronized with each other so that sending scheduling can occur. Time Synchronization Protocol for Sensor Network (TPSN) method is used as a time synchronization method that supports the WSN system. The implementation of TPSN is divided into 2 phase, namely the Discovery Phase and the Synchronization Phase. Functionality testing is carried out so that the system can works as needed. The accuracy testing of time using the TPSN method obtained results of 79.7%. Performance testing of delivery scheduling using the TDMA method shows that the increase in delivery time is 28.37 milliseconds at sensor node 1 and an increase in delivery time is 37.11 milliseconds at sensor node 2.The success rate in delivery using the TPSN and TDMA methods is 96%.